Characterizing the metabolic profile of dexamethasone treated human trabecular meshwork cells. (January 2022) - Graybeal, Kimberly; Sanchez, Luis; Zhang, Chi; Stiles, Linsey; Zheng, Jie J.
Abstract: The trabecular meshwork (TM) is the leading site of aqueous humor outflow in the eye and plays a critical role in maintaining normal intraocular pressure. When the TM fails to maintain normal intraocular pressure, glaucoma may develop. Mitochondrial damage has previously been found in glaucomatous TM cells; however, the precise metabolic activity of glaucomatous TM cells has yet to be quantitatively assessed. Using dexamethasone (Dex) treated primary human TM cells to model glaucomatous TM cells, we measure the respiratory and glycolytic activity of Dex-treated TM cells with an extracellular flux assay. We found that Dex-treated TM cells had quantifiably altered metabolic profiles, including increased spare respiratory capacity and ATP production rate from oxidative phosphorylation. Therefore, we propose that reversing or preventing these metabolic changes may represent an avenue for future research.